2019
DOI: 10.1186/s12891-019-2947-8
|View full text |Cite
|
Sign up to set email alerts
|

Closed reduction of severely displaced radial neck fractures in children

Abstract: BackgroundSeverely displaced radial neck fractures in skeletally immature children are rare and can be difficult to reduce. The purpose of this study is to evaluate the results using our reduction maneuver.MethodsFrom October 2011 to December 2015, 26 children with radial neck fractures(O’Brien type II, III and Judet type III, IV) were treated at our institute. All patients underwent percutaneous K-wire leverage and radial intramedullary pinning in an average surgery time of 35 mins (15–80 min). The injured ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…In children of this age, when radial neck fracture occurs, X-ray often presents only a small piece of metaphyseal bone. It is difficult to judge displacement degree and reduction quality during surgery [ 19 , 20 ]. Doctors and patients also need to receive larger X-ray radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children of this age, when radial neck fracture occurs, X-ray often presents only a small piece of metaphyseal bone. It is difficult to judge displacement degree and reduction quality during surgery [ 19 , 20 ]. Doctors and patients also need to receive larger X-ray radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, in comparison with the k -wire group, the surgical-related indicators and elbow function of the Métaizeau group were signally superior. Based on US and arthrography, modified Métaizeau technique visually reduced the impact on children and improved surgical safety in children with radial neck fractures, accelerating the prognostic speed and effect of children [ 20 , 30 ]. In terms of postoperative complications incidence in two groups, the Métaizeau group was also signally superior.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, closed reduction is the key point for avoiding possible perfusion deficits and healing delays. In completely dislocated fractures, a percutaneously inserted K-wire can manipulate the radial head using a joy-stick-like technique, thus enabling a closed reduction and subsequent ESIN osteosynthesis [ 23 , 24 ]. Some comparative studies have not shown significant differences in the results after closed and open reduction, and this supports the hypothesis that fracture type and initial degree of dislocation are the most important elements for determining functional outcomes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A K-wire may be inserted into the fractured portion of the radial neck, and reduction may be achieved through leverage of the K-wire in conjunction with direct pressure on the radial head with the elbow in flexion or with the Métaizeau technique, which utilizes elastic stable intramedullary nailing (Nancy nailing) for reduction (Figure 11). 45,46 Fracture fixation can then be achieved with either percutaneous pin fixation or with a retrograde elastic nail. 47,48 Distal Radius Distal radius fractures are the most common pediatric fracture seen in the emergency department and comprise nearly one quarter of all pediatric fractures.…”
Section: Proximal Radiusmentioning
confidence: 99%